Reproducibility analysis of the stability and treatment of vertebral metastatic lesions - Pratali,Raphael de Rezende (2014)
OBJECTIVES: To investigate the reproducibility among spine surgeons in defining the treatment of vertebral metastatic lesions, taking into account the mechanical stability of injuries. METHODS: Twenty cases of isolated vertebral metastatic lesions were presented to ten experts. Their opinion was then asked about the stability of the lesion, as well as their treatment option. RESULTS: The interobserver Kappa coefficient obtained both for stability analysis as to the decision of the treatment was poor (0.334 and 0.248, respectively). CONCLUSIONS: Poor interobserver reproducibility was observed in deciding the treatment of vertebral metastatic lesions when considering the stability of the lesions.